PENGARUH STOCK SPLIT TERHADAP KINERJA SAHAM (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2017 – 2021) - Nurlia, Nada Fathina Putri; Hascayani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
A stock split is an activity of splitting a number of outstanding shares of a company to make stocks more liquid so that they can increase transactions from market. The purpose of this study to determine that is any differences between return and trading volume before and after stock splitting. This study uses secondary data that accorded by Investing.com with a research period of 2017 – 2021. The population in this study are companies that performs stock split in the research year determined, that is 64 companies. The sample selection uses a purposive sampling method, so the sample from this research is 61 companies. The result of this study using the Wilcoxon signed rank test, the results is all sectors did not have an increase in stock returns and trading volume after stock splits because investors prioritized company fundamentals rather than stock split announcements. So for companies that want to do a stock split, should improve the company's fundamentals and pay attention to the economic conditions at that time first. This is because investors have other factors to consider in making transactions, one of which is fundamental factors and economic conditions.